Enantioselective cyclopropanation of conjugated cyanosulfones using carbohydrate-based crown ether catalysts. Issue 9 (28th February 2020) - Nemcsok, Tamás; Rapi, Zsolt; Bagi, Péter; Guan, Ying Hou; Orbán, István; Keglevich, György; Bakó, Péter
Abstract: A few new d -galactose- and d -glucose-based monoaza-15-crown-5 type lariat ethers have been synthesized. These macrocycles and their derivatives proved to be efficient catalysts in the cyclopropanation of ( E )-3-phenyl-2-(phenylsulfonyl)acrylonitrile performed with diethyl bromomalonate under mild phase transfer conditions. Among the catalysts tested, the macrocycle having methyl α-d -galactopyranoside unit generated the highest asymmetric induction (80% ee). In the reactions of the aryl-substituted phenylsulfonyl-acrylonitrile derivatives, the cyclopropanation of the meta - and para- substituted starting materials took place with high ee values (75–84% ee). The cyclopropane derivatives synthesized from analogous α, β-unsaturated cyanosulfones containing naphthyl, pyridyl, furyl and thienyl groups were obtained with enantioselectivities up to 85%, and in excellent yields. Graphical abstract: Image 1 Highlights: New d -glucose- and d -galactose-based crown ethers have been synthesized. A new catalyst induced enantioselectivity up to 85% in the MIRC reaction of α, β-unsaturated cyanosulfones. The m - and p -substituted products were formed with 75–84% ee, while the o -substituted cyclopropanes with 0–12% ee. The new chiral cyclopropanes may be important intermediates in asymmetric syntheses.